A transcriptome-wide association study implicates specific pre- and post-synaptic abnormalities in schizophrenia. (6th November 2019) - Hall, Lynsey S; Medway, Christopher W; Pain, Oliver; Pardiñas, Antonio F; Rees, Elliott G; Escott-Price, Valentina; Pocklington, Andrew; Bray, Nicholas J; Holmans, Peter A; Walters, James T R; Owen, Michael J; O'Donovan, Michael C
Abstract: Schizophrenia is a complex highly heritable disorder. Genome-wide association studies (GWAS) have identified multiple loci that influence the risk of developing schizophrenia, although the causal variants driving these associations and their impacts on specific genes are largely unknown. We identify a significant correlation between schizophrenia risk and expression at 89 genes in the dorsolateral prefrontal cortex ( P  ≤ 9.43 × 10 −6 ), including 20 novel genes. Genes whose expression correlate with schizophrenia were enriched for those involved in abnormal CNS synaptic transmission ( P FDR  = 0.02) and antigen processing and presentation of peptide antigen via MHC class I ( P FDR  = 0.02). Within the CNS synaptic transmission set, we identify individual significant candidate genes to which we assign direction of expression changes in schizophrenia. The findings provide strong candidates for experimentally probing the molecular basis of synaptic pathology in schizophrenia.